THE IMPACT OF LOW-FREQUENCY MAGNETIC FIELD ON KETAN TAPE MATURATION: pH, DENSITY, AND TASTE - Masita, Aurora Azzara; Fitria, Rike; Nisabela, Safitri Nuril; Prabandari, Audri Mely; Meilina, Ike Lusi (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2023)
This study explores the novel effect of Extremely Low Frequency (ELF) electromagnetic waves on the fermentation process of sticky rice tape, a traditional Indonesian food made from glutinous rice. ELF electromagnetic waves are waves consisting of magnetic fields and electric fields that do not require intermediaries in their propagation and have frequencies ranging from 0-300 Hz. The study uses a unique experimental method that exposes 2 kg of sticky rice tape, divided into 10 control and 10 experimental samples, each weighing 100 grams and wrapped in ziplock plastic, to ELF electromagnetic waves for two days. The study uses a device that generates ELF electromagnetic waves with a certain intensity and frequency. The study measures the changes in the pH, density, and taste of the sticky rice tape samples after the exposure. The results show that the experimental group’s sticky rice tape had a higher pH, higher density, and sweeter taste than the control group’s sticky rice tape. The study proves the effect of ELF electromagnetic waves on the fermentation process of sticky rice tape and provides insights for the development of new food processing techniques. The study demonstrates the applicability and innovation of using ELF electromagnetic waves for food fermentation.